Unraveling the immunosuppressive microenvironment of glioblastoma and advancements in treatment - Jiang, Dongxin; Li, Yunqian (Frontiers in Immunology, 2025)
Glioblastoma, the most common and aggressive primary brain tumor, remains a significant challenge in oncology due to its immunosuppressive tumor microenvironment (TME). This review summarizes the complex interplay of immune cells and cytokines within the TME, which contribute to immune evasion and tumor progression. We further emphasize the synergistic crosstalk among these components and how it shapes therapeutic vulnerability. Besides, we highlight recent advancements in immunotherapy, including immune checkpoint inhibitors, CAR-T cell therapy, NK cell therapy, oncolytic viruses, and vaccine-based strategies. Despite promising preclinical and clinical results, overcoming the immunosuppressive TME remains a critical hurdle. This review underscores the potential of targeting the TME to enhance therapeutic outcomes in glioblastoma.